La tomba dell’architettura. Il funerale mediatico dell’edificio e della città (Altre Modernità, 2010)
It seems that the process of secularization of our culture has made it impossible for us to legitimate death through its ritualization, thus causing its repression. The article seeks to examine the role played by the media and architecture in a process of re-ritualization of death, especially in their function of filling the void of sacredness, through a symbolic metabolization of the fear of death in our late-modern or post-modern civilization. The relationship between media, death and architecture is particularly frequent, especially in the studies of architecture historians and critics, and it seems to be directly correlated to the media texts' degree of spectacularity. The examination of movies and tv programs reveals the many media discourses that correlate architecture to death: the death of architecture, that is, the death of the building (as in the images of 11/9); the death of urbanism, that is, the death of the cities (in this case, disaster movie genre is the privileged scenario wherein the destruction of the metropolis is spectacularized); and the death of the architect himself (as in Peter Greenaway's movie The Belly of an Architect). The article ends with a brief discussion on the very first corpse of architecture: that is, that of the user, removed from the images of the architectural project, as if it could contaminate the purity of the architect's work of art.
Keywords: MORTE; MEDIA; ARCHITETTURA CONTEMPORANEA; SOCIOLOGIA URBANA